2020
DOI: 10.1371/journal.pone.0243651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bosentan in pulmonary hypertension development in systemic sclerosis patients with digital ulcers

Abstract: Systemic sclerosis is a disease where microcirculation damage is critical in their beginning and vascular complications have similar pathogenic findings. Digital ulcers are a frequent complication in systemic sclerosis patients and pulmonary hypertension is one of the leading causes of death. The use of bosentan has been shown to be useful for the treatment of pulmonary arterial hypertension and to prevent new digital ulcers. However, is unknown if bosentan can prevent pulmonary hypertension. Our objective was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…However, to our knowledge few studies evaluated the incidence of new PAH cases in SSc patients treated with vasoactive drugs because of the presence of DUs. Castellvì et al [21] conducted a retrospective case-control study in 237 SSc patients with previous history of DUs and compared the occurrence of new PH echocardiographic diagnosis in patients treated (n=59) and not-treated (n=163) with bosentan for at least one month. The median treatment duration was of 34 (95% CI 5-59) months.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge few studies evaluated the incidence of new PAH cases in SSc patients treated with vasoactive drugs because of the presence of DUs. Castellvì et al [21] conducted a retrospective case-control study in 237 SSc patients with previous history of DUs and compared the occurrence of new PH echocardiographic diagnosis in patients treated (n=59) and not-treated (n=163) with bosentan for at least one month. The median treatment duration was of 34 (95% CI 5-59) months.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Bosetan did not improve the frequency, duration, pain, or severity of Raynaud's phenomenon, but did significantly improved the functional scores compared to placebo [168]. While no prospective studies have demonstrated efficacy in SSc-PAH, a retrospective study of patients on bosentan for ulcers revealed a significant decrease in PAH incidence [169].…”
Section: Endothelin Receptor Antagonistsmentioning
confidence: 96%
“…Significant change was observed on skin fibrosis, but not on lung involvement [ 84 ]. Bosentan, a dual endothelin-receptor antagonist, has been shown to be useful for the treatment of pulmonary arterial hypertension and to prevent new digital ulcers [ 85 , 86 ]. Sildenafil may reduce proinflammatory activation induced by oxidative stress and can improve the microvascular blood flow in patients with SSc [ 87 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The same effect has not been observed with ARBs [ 103 ]. Dihydropyridine calcium-channel blockers, such as nifedipine, can also reverse SRC [ 86 , 104 ]. Other therapeutic strategies have been tested; plasma-exchange seems to give some benefits, particularly in patients with SRC and microangiopathy or in subjects intolerant to ACE-inhibitors [ 105 , 106 ].…”
Section: Treatmentmentioning
confidence: 99%